Hubungan antara pengetahuan dan perilaku ibu dalam pemberian ASI Eksklusif di Posyandu Tahun 2015 - Natya Ayu Pramudita; Heni Puji Wahyuningsih; Hesty Widyasih (Poltekkes Kemenkes Yogyakarta, 2016)
Infant Mortality Rate in Indonesia is mostly caused by diarrhea and pneumonia.These diseases can be anticipated by givingexclusive breastfeeding to infants. Exclusive breastfeeding has a role in morbidity, mortality, growth and development, andIQ of babies. One of the factors that influence exclusive breastfeeding is knowledge. The percentage of exclusivebreastfeeding in the province in 2013 was66.7% and Bantul Regency is the one experiencing the declining percentage. Thelowest percentage was in the Public Health Center of Sewon I, that is 26.14%. Sewon I Health Center supervises 43Posyandus. Posyandus Menur and Mekarsari are the ones that have the most number of infants aged 6-24 months. Thisstudy aims to determine the relationship between knowledge and behavior of mothers in exclusive breastfeeding. This typeof research is analyticsurvey method with cross-sectional design. The research was held inApril 2015. The instrument usedis questionnaire. The research took place at Posyandu Menur and Mekarsari. These populations are mothers with babiesaged 6-24 months a number of 46 people and the sampling technique used is sampling saturated sampling technique whenail members of the population used as a sample. Results of this study there was no association between knowledge andbehavior with chi-square value of 2.469 (r>-0.116> 0.05). Midwives of Sewon I health center are expected to conduct anevaluation matteraffectingexclusivebreastfeeding beyond the knowledge and the cadres areexpected to provide support tomothers inorder to provide exclusivebreastfeeding.